PENINGKATAN KEMAMPUAN MOTORIK KASAR PADA ANAKUSIA PRASEKOLAH DENGAN KEGIATAN SENAM DI DESAKRANGGANHARJO KECAMATAN TOROH - Sutiyono; Shinta Amalia; Hanny Novita Sari; Erni Pustikha Sari; Meila Cindy Putri Lestari (LPPM AN Nuur, 2023)
Background: 5 year old children are physically very agile and interested in gymnastics and certain sports. To develop the child's physicality through play activities. One of the physical activities to develop children's physical activities is gymnastics. Gymnastics in early childhood includes all the movements. performed following movements and singing to the rhythm of the music that accompanies the exercise. Methodology: The subjects in this research were school children from Kindergarten 1 & 3 Krangganharjo, Toroh District, Grobogan Regency using analysis and demonstration methods. Then, problem-solving solutions are carried out through village community deliberations and then implemented through gymnastics activities. Results: After carrying out the exercise activities, gross motor development in preschool age children increased. Conclusion: Parents' knowledge about gross motor development increases, children can carry out tasks well, children's willingness to participate in gymnastics activities in the development of gross motor skills in preschool children.